Challenges in the definition of input motions for forensic ground-response analysis in the near-source region. Issue 4 (November 2021) - Ntritsos, Nikolaos; Cubrinovski, Misko; Bradley, Brendon A
This article scrutinizes the determination of input motions for forensic ground-response analysis in the near-source region, based on recorded surface ground motions at strong-motion station sites, from the same event. The first part of the article draws upon observed ground motions from the 22 February 2011 6.2 Mw Christchurch earthquake to discuss key challenges of the problem associated with the strong spatial variation of ground motion in the near-source region. Effects from the complexity of the rupture, propagation of seismic waves through complex geological structures, and site characteristics are explored. It is argued that, because of the strongly varying source-path "signature" on near-source ground motions, "reference" input motions for ground-response analysis must be specific to, and have similar signature characteristics (be "compatible") with, the target site which is subject to the analysis. The second part of the article presents a four-step procedure for the derivation of site-specific input motions involving (1) determination of the reference layer where the input motion is to be applied in the analysis, (2) record selection considering the appropriateness of the recording station site for deconvolution and its compatibility with the target site, (3) deconvolution of the selected record to remove local site effects from the recorded ground motion, and (4) scaling of the deconvolved motion to account for differences in the source-to-site distance between the recording station and the target site. As part of the proposed procedure, a novel (amplitude-duration) scaling method is presented. Results from one-dimensional (1D) effective-stress analysis of two target Christchurch sites using input motions from the proposed procedure are used to critically evaluate the procedure and discuss essential requirements for its successful application.